Evaluation of the Relative Viability of Anthropometric Parameters, Aerobic Capacity, Spinal Mobility, Abdominal Muscular Endurance, Back and Lower Limb Muscle Strength in Predicting the Balance Performance of Young Adult Males - Balogun, Joseph A; Odusaga, Felix O; Ojoawo, Adesola O (International Journal of Medical and Health Sciences Research, 2017)
Background: The physical-and-physiological factors that modulate balance performance are currently not well elucidated in the extant literature. Objectives: This study investigated the viability of using demographic factors, physical and physiological variables to predict balance performance. Methods: 150 adult males consented and completed all the 17 tests required. Their anthropometric indices (leg length, thigh and calf circumferences, height, body weight, quotelet index, body surface area), dominant leg isometric muscle strength (quadriceps femoris, hamstrings, plantar flexors and dorsiflexors), spinal mobility (back extension and forward flexion), aerobic capacity, isometric back extensor strength, abdominal muscular endurance and the non-timed criterion unipedal stance performance with eyes opened and eyes closed were measured using standard protocols. Results: Significant positive correlations were obtained between several of the independent variables. Thigh circumference was significantly related to quadriceps femoris strength (r = 0.545, p<0.001), hamstrings strength (r = 0.4.57, p<0.001), plantar flexor strength (r = 0.249, p<0.002), and dorsiflexors strength (r = 0.2496, p<0.002). The 17 independent variables combined contributed significantly (F = 2.051, p<0.05) to the prediction of balance performance with eyes opened. Unexpectedly, only 20.9% of the variance in balance performance was accounted for by the 17 independent variables. Stature and the plantar flexor muscle strength were the two viable predictors of balance performance when the eyes is opened; stature contributed 5.5% and the plantar flexor muscle strength contributed 3.8%. Abdominal muscular endurance contributed 3.1% out of the combined 14.4% variance in balance performance when the eyes are closed. Conclusions: From a practical perspective, the contribution of the 17 physical-and-physiological variables monitored in this study to the prediction of balance performance is dreary; therefore, follow-up studies should explore other independent variables.